Adverse bone health and abnormal bone turnover among perinatally HIV‐infected Asian adolescents with virological suppression1. Issue 4 (1st August 2016) - Sudjaritruk, T; Bunupuradah, T; Aurpibul, L; Kosalaraksa, P; Kurniati, N; Prasitsuebsai, W; Sophonphan, J; Sohn, AH; Ananworanich, J; Puthanakit, T
Abstract : Objectives: This study aimed to determine the prevalence of low bone mass and assess its relationship with abnormal bone turnover among HIV‐infected Asian adolescents. Methods: A multicentre, cross‐sectional study was conducted at four paediatric HIV centres in Thailand and Indonesia. Perinatally HIV‐infected adolescents aged 10–18 years receiving antiretroviral therapy (ART) with virological suppression (HIV RNA < 400 copies/mL) were enrolled. Study assessments included lumbar spine (L2−L4) dual‐energy X‐ray absorptiometry and measurement of bone turnover markers. Bone mineral density (BMD) and bone mineral apparent density (BMAD) Z ‐scores were calculated based on Thai normative age‐ and sex‐matched references. Low bone mass was defined as BMD or BMAD Z ‐scores ≤ −2. Results: Of 396 participants, 57% were female. The median age was 15.0 [interquartile range (IQR) 13.3–16.9] years, and 73% were in Tanner stage 3−5. At enrolment, the median CD4 T‐cell count was 734 (IQR 581–907) cells/μL, and 37% were on protease inhibitor (PI)‐based regimens. The overall prevalence of lumbar spine BMD and BMAD Z ‐scores ≤ −2 were 16.4% and 8.3%, respectively. Z ‐scores were lower with older age, female sex, body mass index (BMI) <5th percentile, boosted PI exposure and CD4 T‐cell percentage < 15% before ART initiation. Increased bone turnover markers were inversely associated with BMD and BMAD Z ‐scores. Conclusions: Low bone mass was linked to older age, female sex, low BMI, boosted PI exposure, and poor immunological status before ART commencement in our cohort of perinatally HIV‐infected Asian adolescents. Dysregulation of bone turnover was associated with bone demineralization. Screening for low bone mass should be implemented to identify individuals who might benefit from interventions to preserve bone health.